Distinct Pattern of Microgliosis in the Olfactory Bulb of Neurodegenerative Proteinopathies - Zacharias Kohl; Johannes C. M. Schlachetzki; Judith Feldewerth; Philipp Hornauer; Martina Münch; Anthony Adame; Markus J. Riemenschneider; Jürgen Winkler; Eliezer Masliah (Neural Plasticity)
The olfactory bulb (OB) shows early neuropathological hallmarks in numerous neurodegenerative diseases, for example, in Alzheimer’s disease (AD) and Parkinson’s disease (PD). The glomerular and granular cell layer of the OB is characterized by preserved cellular plasticity in the adult brain. In turn, alterations of this cellular plasticity are related to neuroinflammation such as microglia activation, implicated in the pathogenesis of AD and PD, as well as frontotemporal lobe degeneration (FTLD). To determine microglia proliferation and activation we analyzed ionized calcium binding adaptor molecule 1 (Iba1) expressing microglia in the glomerular and granular cell layer, and the olfactory tract of the OB from patients with AD, PD dementia/dementia with Lewy bodies (PDD/DLB), and FTLD compared to age-matched controls. The number of Iba1 and CD68 positive microglia associated with enlarged amoeboid microglia was increased particularly in AD, to a lesser extent in FTLD and PDD/DLB as well, while the proportion of proliferating microglia was not altered. In addition, cells expressing the immature neuronal marker polysialylated neural cell adhesion molecule (PSA-NCAM) were increased in the glomerular layer of PDD/DLB and FTLD cases only. These findings provide novel and detailed insights into differential levels of microglia activation in the OB of neurodegenerative diseases.